Effect of rbST on Serum Biochemical Values During Various Physiological and Weather Conditions in Kundhi Buffaloes - Kachiwal, A.B.; Sheikh, B.A.; Sheikh, S.A.; Qureshi, T.A.; Memon, K.H. (Journal of Buffalo Science, 2015)
This study was performed to investigate the effect of rbST treatment on some biochemical parameters in addition to values of thyroid hormones in Kundhi buffaloes. Sixteen Kundhi buffaloes were divided into two groups. Group-A (N=8) served as control and Group-B (N=8) was treated with 250 mg of rbST fortnightly for 1st lactation. Blood samples were collected weekly during lactation period from day one to 60 as pre-treatment values and then from day 61 to completion of 1st lactation in Kundhi buffaloes as post-treatment values. The findings revealed overall non significant variation in the serum biochemical and thyroid hormone values between control and rbST treated buffaloes, whereas, significant differences were observed during various physiological and weather conditions in both groups. Glucose and uric acid values were observed higher during parturition and winter season in Kundhi buffaloes. Protein level was higher in rbST treated buffaloes during open days.